Substitute locations of urban spaces in films shot in Spain: motivations, representations and consequences - Víctor Aertsen; Carlos Manuel Valdés; Antonio Martínez Puche (Boletín de la Asociación de Geógrafos Españoles, 2022)
The objective of the present article is to reflect upon the phenomenon of substitute locations in fiction films, with special focus on Spanish cities. Although the use of one location to stand in for another is a common film practice, it hasn’t received much attention in film studies and related fields. To improve this situation, we start with a brief review of three moments of Hollywood’s history where substitute locations have been central as an industrial practice, cultural debate and promotional strategy, and we propose six parameters that we consider of interest to pursue a detailed analysis of this phenomenon, especially in urban environments. In the second section, we discuss the use of substitute locations in Spanish cities based on the results of a quantitative and qualitative research carried out on 303 films. Finally, as case studies, we focus on examples of substitute locations in films shot in two Spanish cities, Madrid and Alcoy, identifying the main locations and reflecting upon their use in relation to the six parameters proposed in the theoretical framework. Through these different sections, we seek to contribute to a better understanding of the motivations, representations and geographical and economic consequences of this filmic practice.